(untitled) (Journal of Nepal Geological Society, 2000)
This paper deals with landslide hazard mapping in the Nallu Khola watershed of Central Nepal. The study reveals that slope class 30o-40o is highly susceptible to sliding. The highest landslide density is seen on 35° slope with drainage frequency of 40-50 no./km2 Similarly, the lowest landslide density is found associated with the lowest average slope gradient and lowest drainage density. Landslide hazard map shows that the high, medium, and low hazard areas occupy respectively 20%, 45%, and 35% of the watershed. Similarly, the landslide density is the highest in the cells that are categorised as high hazard. The highest number of landslide containing cells in high hazard rank suggests that the forecasted hazard ranks nearly match with the present field conditions. But there are some areas, where forecasted hazard ranks do not match with the present field conditions.